The Value of Nature: Virtue Ethics Perspective - Dursun, Sukru; Mankolli, Hysen (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Virtue ethics is an alternative to consequentialism and deontology. Both consequentialist and deontological theories consider concepts such as “goodness” and “rightness” of action as essential to morality. Virtue ethics, on the other hand, focuses on what kind of person one should be. Virtue ethics proposes to assess the ethical quality of actions in terms of concepts/virtues such as kindness, honesty, sincerity and justice. However, one major problem in environmental ethics is that human societies, as well as culture, are all said to be anthropocentric. This is because the man considers himself as an intellectual being and tries to exercise his control over everything in the environment. Such thinking has led to over-exploitation of the environment – environmental degradation. This has led to the rejection of the anthropocentric worldview by many philosophers. This paper argues against the rejection of the ‘anthropocentric’ worldview. This paper argues that the value of nature cannot be defined in an abstract sense outside of human interaction with nature. Hence, some level of ‘anthropocentricism’ is needed. This paper submits argues that virtue ethics can help solve the environmental problem. This problem can be solved if we construct the attitude of respect for nature as a virtue. Stewardship based on the virtue of respect ought to be the human being’s obligation so that the aim of all nations should become ecologically sound sustainable development.